Inhibition of dendropoiesis by tumor derived and purified prostate specific antigen. - Aalamian, M; Tourkova, I; Chatta, G; Lilja, H; Huland, E; Huland, H; Shurin, G; Shurin, MR (2003)
PURPOSE: Prostate specific antigen (PSA) is a serine protease produced by the prostate gland at high concentrations. Serum PSA may be significantly elevated in prostate cancer and benign prostatic diseases. It has recently become evident that, in addition to being a tissue and/or serum marker, PSA may also have biological effects. Despite the voluminous literature on this biomarker in the diagnosis of prostatic diseases relatively few reports have addressed the issue of the physiological function, biological role and immune effects of PSA in the context of prostate cancer development and progression. MATERIALS AND METHODS: Human dendritic cell (DC) cultures were generated from CD34+ hematopoietic precursors in the presence of PSA. The DC phenotype was assessed by flow cytometry and DC ability to induce T-cell proliferation was detected by allogeneic mixed lymphocyte reaction assay. DCs were also generated in co-cultures with LNCaP cells in the presence of antiPSA antibodies. The concentrations of PSA in cultures were determined by the AXSYM System (Abbott Laboratories, Wiesbaden, Germany). RESULTS: We noted that purified and LNCaP derived PSA inhibited the generation and maturation of DC (dendropoiesis) in vitro, which might have a crucial role in the induction and regulation of specific antitumor immune responses. The addition of active PSA to DC cultures significantly inhibited the generation and maturation of DC, as assessed by the levels of expression of CD83, CD80, CD86 and HLA DR. The ability of DC to induce T-cell proliferation, which depends on the expression of co-stimulatory and major histocompatibility complex molecules, was also suppressed in PSA treated DC cultures. CONCLUSIONS: The antidendropoietic effect of PSA in vitro suggests a new mechanism of prostate cancer induced immunosuppression and tumor escape, and provides novel evidence of the immunoregulatory properties of PSA.